Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

yahooo,suire

  • 3 years ago

6x + 2y = 0 4x + y = -1 substution method please help

  • This Question is Closed
  1. shashi20008
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    in substitution method you find the value of one variable in term of another one from one of the equations and then place the value in 2nd eqn to get the result. in this example, 6x + 2y = 0 => 2y = -6x => y = -3x now placing y = -3x in 2nd eqn 4x + y = -1 => 4x + (-3x) = -1 => 4x -3x = -1 => x = -1 y = -3x = 3

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy